Differential Diagnostic and Therapeutic Tactics of Pleurisy in Pancreatitis and Hepatitis: ABC and ABC/VED Analysis of Pathogenetic Pharmacotherapy - Nevzghoda, Oleksandr; Haiduchok, Ihor; Shapovalov, Valerii (Annals of Mechnikov’s Institute, 2026)
Introduction. Pleurisy associated with pancreatitis and liver diseases is accompanied by malabsorption and deficiency of fat-soluble vitamins, which justifies the use of vitamin pathogenetic pharmacotherapy. At the same time, the structure of the pharmaceutical market of vitamin drugs may not meet real clinical needs, which requires pharmacoeconomic assessment. Purpose. Clinical and pharmaceutical justification of the use of vitamin pharmacotherapy in patients with exudative pleurisy on the background of pancreatitis and hepatitis based on the analysis of the frequency of prescriptions and integrated ABC/VED-analysis of the range of drugs. Materials and methods. A retrospective observational study of 398 patients with exudative pleurisy who underwent inpatient treatment was conducted. The frequency of prescribing vitamin A, vitamin D, vitamin E and vitamin K as part of complex pharmacotherapy was analyzed. The pharmaceutical analysis included a study of the range of vitamin drugs registered in Ukraine using structural ABC analysis, clinically oriented ABC analysis by frequency of prescriptions and VED classification. Results. Established that the range of fat-soluble vitamins is represented by 19 drugs, among which vitamin E drugs dominate (68.42% of positions). Clinical analysis showed that vitamin E was the most frequently prescribed active pharmaceutical ingredient in patients with pancreatogenic and hepatogenic pleurisy. Integrated ABC/VED analysis identified vitamin E drugs as the priority category AV, while vitamin D and vitamin A formed the BE group, and vitamin K - the CD group. A discrepancy between the structure of the pharmaceutical market and the real clinical need was revealed, which indicates the duplication of trade names of vitamin E preparations.